(untitled) (Bioscience Journal, 2017)
To evaluated the chemical composition and ruminal degradability of crambe byproducts (meal and crushed) and proteic supplements formulated with crushed crambe (0; 2.5; 5; 10 and 15%); five crossbred steers with average weight of 485±14 kg, were used. All the animal were kept in individual paddocks of 0.25 ha on Urochloa brizantha (syn. Brachiaria brizantha). It was observed a greater soluble fraction, higher effective degradability at 5%/h and higher degradation rate “c” and, consequent, lower indigestible fraction for crambe crushed ground in the sieve of 3 mm. The effective degradability at 5%/h was lower for the crambe crushed (55.42) in relation to the meal (48.80). The diet with 5% of inclusion of crambe showed higher effective degradability for dry matter (54.86%) and lower fraction “I” (30.64%) associated with higher fractions “c” and “b”. Crambe ground in sieves of 1 and 3 mm mesh presented the highest degradability. Crushed crambe showed higher ruminal degradation than crambe meal; the crambe byproducts possibility can be use as a source of non-degradable protein in the rumen.